A source of resistance against yellow mosaic disease in soybeans correlates with a novel mutation in a resistance gene - Rahman, Saleem Ur; Raza, Ghulam; Naqvi, Rubab Zahra; McCoy, Evan; Hammad, Muhammed; LaFayette, Peter; Parrott, Wayne Allen; Amin, Imran; Mukhtar, Zahid; Gaafar, Abdel-Rhman Z.; Hodhod, Mohamed S.; Mansoor, Shahid (Frontiers in Plant Science, 2023)
Yellow mosaic disease (YMD) is one of the major devastating constraints to soybean production in Pakistan. Here, we report the identification of resistant soybean germplasm and a novel mutation linked with disease susceptibility. Diverse soybean germplasms were screened to identify YMDresistant lines under natural field conditions during 2016-2020. The YMD severity was recorded based on symptoms and was grouped according to the disease rating scale 0-5 and, named as highly resistant (HR), moderately resistant (MR), resistant (R), susceptible (S), moderately susceptible (MS), and highly susceptible (HS). A HR plant named "NBG-SG Soybean" was identified, which showed stable resistance for five years (2016-2020) at the experimental field of the National Institute for Biotechnology and Genetic Engineering (NIBGE), Faisalabad, a hot spot area for virus infection. HS soybean germplasm was also identified as NBG-47 (PI628963), NBG-117 (PI548655), SPS-C1 (PI553045), SPS-C9 (PI639187), and cv. NARC-2021, etc. The YMD adversely affected the yield and a significant difference was found in the potential yield of NBG-SG-soybean (3.46±0.13 a t/ha) with HS soybean germplasm; NARC-2021 (0.44±0.01 c t/ha) and NBG-117 (1.12±0.01 d t/ha), respectively. The YMD incidence was also measured each year (2016-2020) and data showed a significant difference in the percent disease incidence in the year 2016 and 2018 and decreased after 2019 when resistant lines were planted. The resistance in NBG-SG soybean was further confirmed by testing for an already known mutation (SNP at 149 th position) for YMD in the Glyma.18G025100 gene of soybean. The susceptible soybean germplasm in the field was found positive for the said mutation. Moreover, an ortholog of the CYR-1 viral resistance gene from black gram was identified in soybean as Glyma.13G194500 that has a novel deletion (28bp/90bp) in the 5`UTR of susceptible A source of resistance against yellow mosaic disease in soybean correlates with a novel mutation in resistance 2 germplasm. The characterized soybean lines from this study will assist in starting soybean breeding programs for YMD resistance. This is the first study regarding screening and molecular analysis of soybean germplasm for YMD resistance.Methods and MaterialsA total of 1,007 soybean accessions were screened during the period of 2016-2020.